Identification of microplastic content in milkfish ponds in Lontar Village, Serang Regency - Yogi, Yonita Nabila; Putra, Achmad Noerkhaerin; Aryani, Desy (Universitas Malikussaleh, 2024)
Microplastics measuring < 5 mm can easily enter the fish's body through the respiratory system and digestive system. The aim of this research is to calculate the abundance of microplastics and determine the types contained in the bodies of milkfish, water and sediment in the Lontar Village Pond, Serang Regency. There are 6 stations, 4 fish samples were taken from each station, water samples were taken using a plankton net and sediment samples were taken using individual pipes at each station. The number of fish samples was 24 fish, meat, intestine, stomachs and gills were taken. Fish organs were destroyed using 10% KOH. Samples were incubated for 24 hours until the organic material was destroyed. Then filtered using Whattman No 42, and dried using an oven at 60ºC for 1 hour. Likewise, filtering of water and sediment samples is carried out. The types of microplastics found were fragments, fibers and films. The highest abundance was in the gills and intestines with an abundance of 11 per individual. The highest abundance of microplastics in the water in Lontar Village ponds is the fragment type with a total of 5 per/20 mL at station 3 and the film type with a total of 5 per/20 mL at station 6 and in the milkfish pond sediments of Lontar Village the highest abundance of microplastics is 1 per/25 gr. The types of polymers found in the digestive tract of milkfish are Polycarbonate (PC), Acrylonitrile butadiene styrene (ABS), Latex, Polystyrene (PS), Nylon, and Polytetrafluoroethylene (PTFE).Keywords: Aquaculture; Lontar; Microplastics; Milkfish